Resale Price Maintenance and Forward Integration into a Monopolistically Competitive Industry - Perry, Martin K.; Groff, Robert H. (Quarterly Journal of Economics, 1985)
In this paper we adopt the CES model of product differentiation for the downstream stage of the industry. With an upstream monopolist we first show that resale price maintenance is equivalent to forward integration and that both increase profits. Then we demonstrate that forward integration by an upstream monopolist will reduce welfare for the industry. Prices fall with forward integration, but the integrating firm contracts the number of downstream subsidiaries so drastically that the reduced diversity more than offsets the gains from lower prices.